Creating an innovative youth mental health service in the United Kingdom: The Norfolk Youth Service. Issue 4 (4th August 2017) - Wilson, Jon; Clarke, Tim; Lower, Rebecca; Ugochukwu, Uju; Maxwell, Sarah; Hodgekins, Jo; Wheeler, Karen; Goff, Andy; Mack, Robert; Horne, Rebecca; Fowler, David
Abstract : Young people attempting to access mental health services in the United Kingdom often find traditional models of care outdated, rigid, inaccessible and unappealing. Policy recommendations, research and service user opinion suggest that reform is needed to reflect the changing needs of young people. There is significant motivation in the United Kingdom to transform mental health services for young people, and this paper aims to describe the rationale, development and implementation of a novel youth mental health service in the United Kingdom, the Norfolk Youth Service. The Norfolk Youth Service model is described as a service model case study. The service rationale, national and local drivers, principles, aims, model, research priorities and future directions are reported. The Norfolk Youth Service is an innovative example of mental health transformation in the United Kingdom, comprising a pragmatic, assertive and "youth‐friendly" service for young people aged 14 to 25 that transcends traditional service boundaries. The service was developed in collaboration with young people and partnership agencies and is based on an engaging and inclusive ethos. The service is a social‐recovery oriented, evidence‐based and aims to satisfy recent policy guidance. The redesign and transformation of youth mental health services in the United Kingdom is long overdue. The Norfolk Youth Service represents an example of reform that aims to meet the developmental and transitional needs of young people at the same time as remaining youth‐oriented.